Поєднання раку щитоподібної залози та тиреотоксикозу - Бурдо, І. С.; Комісаренко, І. В.; Гуда, Б. Б. (Clinical Endocrinology and Endocrine Surgery, 2011)
Article describes the peculiarity of thyrotoxicosis development in case of thyroid gland cancer and thyrotoxicosis combination. Between 1989 and 2003 surgical treatment of hyperthyroidism in 1843 patients (189 children and adolescents, 1654 adult patients) was made. During that period, 1094 (59.3%) patients underwent subtotal thyroidectomy and 551 (29.8%) patients underwent near total thyroidectomy. A total thyroidectomy was performed in 198 (10.7%) cases. Differentiated thyroid cancer carcinoma (papillary carcinoma in 41 cases, follicular carcinoma in 15 cases) was discovered as an incidental finding in 3.3% adult patients and in 1% children and adolescents, but none of them developed metastasis during the follow-up period. Reccurence of thyroid cancer it has not been revealed.